2021
DOI: 10.3389/fphar.2021.664181
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–Glucose CoTransporter-2 Inhibitor Empagliflozin Ameliorates Sunitinib-Induced Cardiac Dysfunction via Regulation of AMPK–mTOR Signaling Pathway–Mediated Autophagy

Abstract: Background: Sodium–glucose cotransporter-2 (SGLT2) inhibitors have been shown to decrease the adverse cardiac events and risks of cardiovascular mortality among patients with or without diabetes, which has made these drugs promising treatment options for patients with chronic heart failure. Cardiac dysfunction is a common and severe side effect induced by cancer chemotherapies, which seriously affects the prognosis and life quality of tumor patients. However, it is not clear whether SGLT2 inhibitors have cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 43 publications
2
47
0
1
Order By: Relevance
“…6 d). To further confirm effects of si-TFAF6 on LPS plus ATP-induced changes in autophagy, BV2 cells were transfected with mCherry-GFP-LC3 adenovirus to observe autophagic flow as reported [ 28 ]. Results showed that LPS plus ATP stimulation triggered a dramatic decrease in autophagosomes (yellow puncta) and autolysosomes (red puncta) in BV2 cells, and si-TRAF6 transfection reversed the result with more autolysosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 d). To further confirm effects of si-TFAF6 on LPS plus ATP-induced changes in autophagy, BV2 cells were transfected with mCherry-GFP-LC3 adenovirus to observe autophagic flow as reported [ 28 ]. Results showed that LPS plus ATP stimulation triggered a dramatic decrease in autophagosomes (yellow puncta) and autolysosomes (red puncta) in BV2 cells, and si-TRAF6 transfection reversed the result with more autolysosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used mCherry green fluorescent protein (GFP)-tagged LC3 adenovirus (AdmCherry-GFP-LC3) (Hanbio, China) to observe the change in autophagy as previously reported [ 28 ]. Green fluorescence will be quenched when GFP enters the acidic environment in lysosomal.…”
Section: Methodsmentioning
confidence: 99%
“… 76 In a series of experimental studies, SGLT2 inhibitors were reported to inhibit the mTOR signalling pathway and thereby maintain redox homeostasis, upregulate autophagy, and suppress inflammation, which may partially explain the cardiorenal protective mechanisms induced by SGLT2 inhibition. 76 , 117 , 118 , 119 , 120 , 121 …”
Section: Cardiorenal Protection Of Sglt2 Inhibitor Based On Metabolic...mentioning
confidence: 99%
“…Several pathways are reported in improving the myocardial cell’s autophagy deficiency of diabetes, such as the activation of AMPK ( Aragon-Herrera et al, 2019 ) and through the microRNA-30d/KLF9/VEGFA pathway ( Zhang et al, 2020 ). SGLT2 inhibitors are also reported to suppress mTORC1 formation ( Ren et al, 2021 ) and activate SIRT1 ( Packer, 2020b ) and HIF-2α ( Packer, 2020a ) of myocardial cells, which could contribute to the improvement of autophagy.…”
Section: Effect Of Sodium–glucose Cotransporter 2 Inhibitors On Autophagy In Each Organmentioning
confidence: 99%